Palm Sugar Marketing Strategy Based On Swot Analysis In Improving Community Welfare In Cipeuteuy Village, Darmaraja Districta - Fadilah, Ahmad; Amelia, Mimma; Alifah, , Riflina Reva; Fatturohman, Rio; Darmawan, Tasya Salsabila; Sezilian, Ziila Keisha; Wangi, Sekar (Journal of Bussines Management Basic, 2025)
This research analyzes palm sugar marketing strategies based on SWOT analysis in improving community welfare in Cipeuteuy village, Darmaraja District, using a qualitative approach through observation, interviews and documentation. Palm Sugar SMEs have significant potential opportunities but face problems in marketing strategy and product innovation. The research results prove that the Cipeuteuy Village Palm Sugar UKM, Darmaraja District, has succeeded in innovating by creating regional natural products that provide added value and market appeal. The application of SWOT analysis has made it easier to identify various opportunities, threats, strengths and weaknesses to improve community welfare. The main challenges include decreasing demand due to the large number of competitors, and not yet implementing innovation in marketing strategies and products. The research results show that consumers show a strong preference for choosing hygienic products, natural raw materials and excellent service, by analyzing SWOT to make products superior to other markets. The overall research results prove that the Palm Sugar UKM in Cipeuteuy Village, Darmaraja District, has succeeded in empowering local business potential with marketing strategies through SWOT analysis for community welfare, providing an example by innovating and utilizing the nature that exists in areas with potential business opportunities